Análise dos relacionamentos em cadeia de suprimentos internacionais: um estudo na multinacional brasileira Marfrig e suas subsidiárias - Storti, Adriana Troczinski (Universidade do Vale do Rio dos Sinos, 2012)
Studies aimed at the understanding the characteristics of relationships that occur among companies involved in supply chain is timely when it grows the performance of overseas companies. This research focused on the analysis of the relationship with a supply chain from a Brazilian multinational, specifically the Marfrig Group. It describes the relationships established in domestic supply chain in the city of São Gabriel (in Rio Grande do Sul Brazil) and international supply chain existent between the slaughterhouse Tacuarembó (namesake city, in Uruguay) Uruguay, and in the slaughterhouse Quickfood Argentina (in Buenos Aires, Argentina). This research aims to understand and compare the presence and alignment of information in the analysis criteria cooperation, involvement, trust, coordination and communication in the supply chain relationships in Brazil, Argentina and Uruguay, a multinational based in Brazil. It was developed an analytical model and through interviews with members of these chains, acontent analysis using a software appropriated to qualitative data was used. Findings point out low presence and lack of alignment of information in several categories of analysis, which may prejudice new strategies in the supply chain perspective. For this reason, there is the necessity of actions that encourage and foster trust, cooperation, involvement, coordination and communication, in the perception of those involved in the research process, in accordance with the strategic objectives of the headquarters.
Keywords: Relacionamentos; Cadeia de suprimentos; Multinacional; Carne bovina; Relationships; Supply chain; Multinational; Beef; ACCNPQ::Ciências Sociais Aplicadas::Administração